SISTEM PAKAR DIAGNOSA PENYAKIT AYAM RAS PETELUR - Nur Aminudin; Taufiq Taufiq; Inti Barokah Amaliah (Jurnal TAM (Technology Acceptance Model), 2019)
sophisticated era, especially in the field of computer inspire for the making of computer application System Expert Diagnosis of Chicken Layer layer Disease. The purpose of this study is to create a website application that can be used by laymen either rural farmers or experts who want to add insight into the various symptoms and diseases that attack livestock. There are 45 symptoms that produce 15 diagnoses of disease caused by viruses and bacteria. The programming language used in the design of this expert system is PHP. Meanwhile for the author database using MySQL. The methodology used to develop software is Waterfall. Meanwhile, to build this expert aplikation writer using a website-based application and the results of this expert application can provide solutions in the form of prevention, how to treatment, and drugs that must be used so as to cope with the disease early on.